8/x+9-(2/x-3)=0
Step by step solution :
Step 1 :
2
Simplify —
x
Equation at the end of step 1 :
8 2
(— + 9) - (— - 3) = 0
x x
Step 2 :
Rewriting the whole as an Equivalent Fraction :
2.1 Subtracting a whole from a fraction
Rewrite the whole as a fraction using x as the denominator :
3 3 • x
3 = — = —————
1 x
Equivalent fraction : The fraction thus generated looks different but has the same value as the whole
Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator
Adding fractions that have a common denominator :
2.2 Adding up the two equivalent fractions
Add the two equivalent fractions which now have a common denominator
Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:
2 - (3 • x) 2 - 3x
——————————— = ——————
x x
Equation at the end of step 2 :
8 (2 - 3x)
(— + 9) - ———————— = 0
x x
Step 3 :
8
Simplify —
x
Equation at the end of step 3 :
8 (2 - 3x)
(— + 9) - ———————— = 0
x x
Step 4 :
Rewriting the whole as an Equivalent Fraction :
4.1 Adding a whole to a fraction
Rewrite the whole as a fraction using x as the denominator :
9 9 • x
9 = — = —————
1 x
Adding fractions that have a common denominator :
4.2 Adding up the two equivalent fractions
8 + 9 • x 9x + 8
————————— = ——————
x x
Equation at the end of step 4 :
(9x + 8) (2 - 3x)
———————— - ———————— = 0
x x
Step 5 :
Adding fractions which have a common denominator :
5.1 Adding fractions which have a common denominator
Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:
(9x+8) - ((2-3x)) 12x + 6
————————————————— = ———————
x x
Step 6 :
Pulling out like terms :
6.1 Pull out like factors :
12x + 6 = 6 • (2x + 1)
Equation at the end of step 6 :
6 • (2x + 1)
———————————— = 0
x
Step 7 :
When a fraction equals zero :
7.1 When a fraction equals zero ...
Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.
Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.
Here's how:
6•(2x+1)
———————— • x = 0 • x
x
Now, on the left hand side, the x cancels out the denominator, while, on the right hand side, zero times anything is still zero.
The equation now takes the shape :
6 • (2x+1) = 0
Equations which are never true :
7.2 Solve : 6 = 0
This equation has no solution.
A a non-zero constant never equals zero.
Answer:
The total cost of producing 91 units of ACME rocket fuel is $3999.99.
Step-by-step explanation:
The Marginal Cost is given by the following function

The total cost function is the integrative of the marginal cost function. So:



In which K, the integrative constant, is the fixed cost. So
.
1. Find the total cost of producing 91 units of ACME rocket fuel.
This is TC(91).
So

The total cost of producing 91 units of ACME rocket fuel is $3999.99.
The answer
the sum of the angles in a triangle is always 180°
m < B + m < A + m < C = 180°,
let's find m < B,
by applying sinus rule
14/sinB=10/sinC, so sinB= 10xsinB = 14 x sinC and therefore,
sinB=( 14/10 )sinC =7/2 sin 36° =0.82, so arcsinB=55.08°
the answer is C 55.4°
Answer:
c i think
Step-by-step explanation:
The answer is 34% of (US$ 1000) = <span>340 US$
~hope this helps! :D</span>